Establishment of a novel method to assess MEK1/2 inhibition in PBMCs for clinical drug development - Schüssele, Lara M.; Koch-Heier, Julia; Volk, Julian; Löffler, Markus W.; Hoffmann, Katharina; Bruyns, Regina M.; Planz, Oliver (Frontiers in Cell and Developmental Biology, 2022)
The Raf/MEK/ERK signaling pathway plays a key role in regulating cellular proliferation, differentiation, apoptosis, cytokine production, and immune responses. However, it is also involved in diseases such as cancer, and numerous viruses rely on an active Raf/MEK/ERK pathway for propagation. This pathway, and particularly MEK1/2, are therefore promising therapeutic targets. Assessment of target engagement is crucial to determine pharmacodynamics or the efficacy of a MEK1/2 inhibitor. In the field of infectious diseases, this is usually done in clinical trials with healthy probands. One method to detect MEK1/2 inhibitor target engagement is to assess the degree of ERK1/2 phosphorylation, as ERK1/2 is the only known substrate of MEK1/2. As healthy subjects, however, only feature a low baseline MEK1/2 activation and therefore low ERK1/2 phosphorylation in most tissues, assessing target engagement is challenging, and robust methods are urgently needed. We hence developed a method using PBMCs isolated from whole blood of healthy donors, followed by ex vivo treatment with the MEK1/2 inhibitor zapnometinib and stimulation with PMA to first inhibit and then induce MEK1/2 activation. As PMA cannot activate MEK1/2 upon MEK1/2 inhibition, MEK1/2 inhibition results in impaired MEK1/2 activation. In contrast, PMA stimulation without MEK1/2 inhibition results in high MEK1/2 activation. We demonstrated that, without MEK1/2 inhibitor treatment, MEK1/2 stimulation with PMA induces high MEK1/2 activation, which is clearly distinguishable from baseline MEK1/2 activation in human PBMCs. Furthermore, we showed that treatment with the MEK1/2 inhibitor zapnometinib maintains the MEK1/2 activation at approximately baseline level despite subsequent stimulation with PMA. As our protocol is easy to follow and preserves the cells in an in vivo-like condition throughout the whole handling process, this approach can be a major advance for the easy assessment of MEK1/2 inhibitor target engagement in healthy probands for clinical drug development.